Positive grid line silver-aluminum paste for N-type IBC battery, N-type IBC battery and preparation method of N-type IBC battery
By using silver aluminum paste in N-type IBC batteries, including organic additives, silver powder, aluminum powder, boron powder and gallium powder, high temperature sintering to form a positive gate line, solving the passivation layer failure caused by laser groove and metal composite center. The problem is that the open circuit voltage and efficiency of the battery are improved.
Patent Information
- Application Number
- CN202310701302.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-13
AI Technical Summary
The existing N-type IBC batteries require laser grooves before printing the positive gate lines, resulting in damage to the passivation layer and the formation of the metal composite center, reducing the open circuit voltage.
Use silver aluminum paste, and the components include organic additives, silver powder, aluminum powder, boron powder, gallium powder and glass powder. The positive gate line is formed by high-temperature sintering, eliminating the laser groove step, and reducing aluminum by using the specific gravity and chemical characteristics of gallium. Side effects, improving Ga-Si contact probability and battery efficiency.
It improves the open circuit voltage and efficiency of the battery, reduces the side effects of aluminum, avoids the damage to the passivation layer by laser grooves, and extends the service life of the battery.
Smart Images

Figure CN119132693A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an N-type IBC cell positive grid line silver-aluminum paste, an N-type IBC cell and a preparation method thereof. Background Art
[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-regions and n-regions arranged in an interdigitated shape on the back of the battery.
[0003] At present, N-type IBC batteries use N-type original silicon wafers, and the P+ area uses boron diffusion superimposed laser SE technology to reduce metal recombination and increase the opening voltage.
[0004] In the preparation process of the above-mentioned N-type IBC battery, the N-type IBC battery still needs to perform laser grooving on the P+ region before printing the grid line to facilitate printing of aluminum paste to form the positive grid line. However, laser grooving not only increases the production process, but also damages the passivation layer. In the cooling process after sintering, the aluminum element in the aluminum paste diffuses into the PN junction, easily forming a metal composite center, resulting in a decrease in the open circuit voltage value of the battery. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an N-type IBC battery positive electrode grid line silver aluminum paste, an N-type IBC battery and a preparation method thereof, so as to solve the problem that the existing N-type IBC battery aluminum paste needs to be laser grooved in the P+ area before printing into the positive electrode grid line, and is prone to form a metal composite center, resulting in a decrease in the open circuit voltage value of the battery cell.
[0006] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0007] The present invention provides a silver-aluminum paste for positive grid lines of N-type IBC batteries, wherein the components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder.
[0008] Furthermore, in the silver-aluminum paste of the N-type IBC battery, the mass fractions of the organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 0.8-1.5%, 65-75%, 2-5%, 0.1-0.3%, 0.1-0.2%, 15.5-30.2% and 1.8-2.5%, respectively.
[0009] Furthermore, in the silver aluminum paste, the glass powder includes 15 to 25% by mass of Bi 2 O3 , 4-8% Al 2 O 3 , 6~12% SiO 2 , 10-29% ZnO, 15-20% Pb 2 O 5 , 4-8% TiO 2 4-10% B 2 O 3 and 15-28% TeO 3 .
[0010] Furthermore, in the silver-aluminum paste, the gallium powder is single-element gallium.
[0011] Furthermore, in the silver-aluminum paste, the organic additive includes one or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.
[0012] Furthermore, in the silver-aluminum paste, the organic binder includes a high molecular polymer resin and an organic solvent;
[0013] The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%;
[0014] The mass fraction of the organic solvent in the organic binder is 88-92%.
[0015] Furthermore, in the silver-aluminum paste, the high molecular polymer is resin-50;
[0016] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0017] Furthermore, in the silver-aluminum paste, the silver powder includes micron-spherical silver powder and nano-spherical silver powder;
[0018] And / or the aluminum powder includes micron-sized spherical aluminum powder with a mass fraction of 82-92% and a D50 of 5-6 μm, and micron-sized spherical aluminum powder with a mass fraction of 8-18% and a D50 of 9-10 μm.
[0019] The present invention also provides a method for preparing an N-type IBC battery, which comprises:
[0020] After forming an n+ doped region and a p+ doped region arranged in an interdigitated manner on the back of an N-type silicon wafer, a passivation layer is formed on the surface of the n+ doped region and the p+ doped region;
[0021] Printing silver-aluminum paste on a first region of the passivation layer, and printing silver paste on a second region of the passivation layer; a projection of the first region is within the range of the p+ doped region, and a projection of the second region is within the range of the n+ doped region; wherein the components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder;
[0022] The N-type silicon wafer with silver-aluminum paste printed on the first area and silver paste printed on the second area is sintered at high temperature to produce an IBC battery.
[0023] The present invention also provides an N-type IBC battery, wherein the N-type IBC battery is prepared by the method as described above.
[0024] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0025] In the embodiment of the present invention, the silver-aluminum paste for the positive grid line of an N-type IBC battery provided comprises an organic additive, silver powder, aluminum powder, boron powder, gallium powder, an organic adhesive and glass powder. Among them, the boron element in the boron powder can increase the doping of the P+ region; gallium and aluminum are both third main group elements, and have similar chemical properties to aluminum, and can replace part of the aluminum powder; and the silver powder has a burn-through effect. After forming a passivation layer on the back of the battery silicon wafer, it is directly printed on the passivation layer area above the p+ doped area, and then subjected to high-temperature sintering, it can contact the p+ doped area and form a positive grid line, eliminating the step of secondary laser grooving, avoiding damage to the passivation layer caused by the secondary laser grooving, and can increase the open circuit voltage of the battery; at the same time, the specific gravity of gallium is relatively large, and it drops to the silicon surface faster than aluminum during the sintering process. The surface is formed, which increases the Ga-Si contact probability, reduces aluminum as a recombination center, reduces the contact resistance between the paste and the battery, and can maintain a high open circuit voltage; in addition, gallium is used to replace part of the aluminum powder, which reduces the aluminum content, helps to reduce the side effects of Al, weakens the Al-Si reaction, and forms shallower silver-aluminum corrosion pits and reduces recombination, thereby improving the open circuit voltage and efficiency of the battery; thus solving the problem that the existing N-type IBC battery aluminum paste needs to be laser grooved in the P+ area before printing the positive electrode grid line, and is prone to form a metal recombination center, resulting in a decrease in the open circuit voltage value of the battery cell.
[0026] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a flow chart of a method for preparing silver-aluminum paste for positive grid lines of N-type IBC batteries provided by an embodiment of the present invention;
[0028] Figure 2It is a flow chart of a method for preparing an N-type IBC battery provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] The applicant of the present invention has found that the main component of the metallization printing paste of the current N-type IBC is aluminum paste, which will cause great metal complexation to the battery cell itself, increase the series resistance of the battery cell, reduce the electrical performance of the battery cell itself, and lead to low opening voltage, large series resistance, and poor filling, which can easily affect the efficiency of the battery cell itself.
[0031] In order to solve the above problems, an embodiment of the present invention provides a silver-aluminum paste for positive grid lines of an N-type IBC battery, wherein the components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder.
[0032] The silver-aluminum paste for the positive grid line of an N-type IBC battery provided in an embodiment of the present invention is used to form the positive grid line of an N-type IBC battery, specifically, to form the positive grid line of an N-type IBC battery whose back side is formed with a P+ region by boron diffusion superimposed on a laser SE technology.
[0033] Among them, silver powder and aluminum powder are the main components. Aluminum powder mainly replaces the P+ emitter of the battery. Silver has good burn-through performance, and gallium and aluminum are both third-group elements, with similar chemical properties to aluminum. Not only can it play a doping role, but also gallium has a larger specific gravity and reaches the silicon wafer surface before aluminum during the sintering process, reducing aluminum as a composite center; therefore, when the aluminum paste is printed on the passivation layer on the back of the N-type silicon wafer, the silicon nitride film and the silicon oxide film in the passivation layer can be burned through in turn, and then contact with the p+ doped area to form a positive gate line, eliminating the step of secondary laser grooving and avoiding the damage of the passivation layer caused by the secondary laser grooving;
[0034] Among them, boron powder can diffuse into the silicon during high-temperature sintering for heavy doping, which is beneficial to improve the contact performance of the slurry and reduce the reaction contact surface between aluminum and silicon;
[0035] Among them, glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic adhesive can ensure the overall bonding effect; organic additives can reduce the overall viscosity of silver aluminum paste.
[0036] Therefore, the silver-aluminum paste provided in the embodiment of the present invention has better contact with the battery cell itself, and the series resistance is smaller than that of traditional aluminum paste. The recombination rate and degree of recombination will also be greatly improved, and the opening voltage of the battery can be increased by 5 millivolts, thereby solving the problem that the existing N-type IBC battery needs to perform laser grooving on the P+ area when printing the positive electrode grid line, and is prone to form a metal recombination center, resulting in a decrease in the open circuit voltage value of the battery cell.
[0037] Optionally, in one embodiment, in the silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 0.8-1.5%, 65-75%, 2-5%, 0.1-0.3%, 0.1-0.2%, 15.5-30.2% and 1.8-2.5%, respectively. In the silver-aluminum paste provided by the embodiment of the present invention, the aluminum content is relatively low. When forming the aluminum-silicon alloy, the proportion of aluminum in the aluminum-silicon alloy is relatively small, so during the cooling process, no excess aluminum will diffuse into the PN junction area to form a metal composite area.
[0038] Optionally, in one embodiment, in the above-mentioned silver-aluminum paste, the mass fractions of organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder are 1.0-1.2%, 68-72%, 3-4%, 0.15-0.25%, 0.12-0.18%, 20-25% and 2.0-2.2%, respectively.
[0039] For example, in the above silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 0.8%, 75%, 2%, 0.3%, 0.1%, 20% and 1.8% respectively.
[0040] For example, in the above silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 1.5%, 65%, 5%, 0.1%, 0.2%, 25.7% and 2.5% respectively.
[0041] For example, in the above-mentioned silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 1.1%, 70%, 3%, 0.2%, 0.15%, 23.45% and 2.1% respectively.
[0042] For example, in the above silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 1.5%, 75%, 5%, 0.3%, 0.2%, 15.5% and 2.5% respectively.
[0043] For example, in the above silver-aluminum paste, the mass fractions of organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic binder and glass powder are 0.8%, 65%, 2%, 0.1%, 0.1%, 30.2% and 1.8% respectively.
[0044] Optionally, in one embodiment, the gallium powder is micron-sized single substance indium, specifically micron-sized single substance gallium with a purity of 2 nines.
[0045] Optionally, in one embodiment, the gallium powder is a gallium-aluminum alloy.
[0046] Optionally, in one embodiment, the boron powder includes micron-sized elemental boron. By adding the micron-sized elemental boron, the boron powder can quickly diffuse into the silicon for heavy doping during high-temperature sintering, which is beneficial to improving the contact performance of the slurry.
[0047] Optionally, in a specific embodiment, the boron powder is micron-grade boron powder with a purity of 3 9s.
[0048] Optionally, in one embodiment, the aluminum powder includes micron-sized spherical aluminum powder with a mass fraction of 82-92% and a D50 of 5-6 μm, and micron-sized spherical aluminum powder with a mass fraction of 8-18% and a D50 of 9-10 μm. The grading of aluminum powders with different particle sizes can supplement and penetrate into the gaps between micron-sized particles.
[0049] Optionally, in a specific embodiment, the aluminum powder includes 82-92% by mass of micron-sized spherical aluminum powder and 8-18% by mass of nano-sized spherical aluminum powder.
[0050] Optionally, in a specific embodiment, the aluminum powder includes micron-sized spherical aluminum powder with a purity of 3 9s, a mass fraction of 82-92%, and a D50 of 5-6 μm, and nano-sized spherical aluminum powder with a purity of 3 9s, a mass fraction of 8-18%, and a D50 of 9-10 nm.
[0051] Optionally, in one embodiment, the silver powder includes micron-sized spherical silver powder and nano-sized spherical silver powder. Since there are gaps between the micron-sized silver powder and the silver powder, the nano-sized spherical silver powder can just fill and penetrate into the gaps between the micron-sized silver powder.
[0052] Optionally, in a specific embodiment, the silver powder includes 82-92% by mass of micron-sized spherical silver powder and 8-18% by mass of nano-sized spherical silver powder.
[0053] Optionally, in a specific embodiment, the silver powder includes micron-sized spherical silver powder with a purity of 3 9s, a mass fraction of 82-92%, and a D50 of 5-6 μm, and nano-sized spherical silver powder with a purity of 3 9s, a mass fraction of 8-18%, and a D50 of 9-10 nm.
[0054] Optionally, in one embodiment, the organic auxiliary agent includes one or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, lauryl alcohol phosphate mixture, Digo 655, and BYKl09.
[0055] In the silver-aluminum paste for the positive grid line of an N-type IBC battery provided in an embodiment of the present invention, the above-mentioned organic binder includes a polymer resin and an organic solvent; wherein the polymer resin is dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role of bonding powder after drying.
[0056] Optionally, in one embodiment, the mass fraction of the high molecular weight polymer in the organic binder is 8-12%; the mass fraction of the organic solvent in the organic binder is 88-92%.
[0057] Optionally, in some embodiments, the mass fraction of the high molecular weight polymer in the organic binder is 9 to 11%; the mass fraction of the organic solvent in the organic binder is 89 to 91%.
[0058] Optionally, in one embodiment, the high molecular weight polymer is ethyl cellulose-N20, ethyl cellulose N-50, ethyl cellulose-N100, resin-50, etc.;
[0059] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0060] Optionally, in one embodiment, the glass powder includes 15-25% by mass of Bi 2 O 3 , 4-8% Al 2 O 3 , 6~12% SiO 2 , 10-29% ZnO, 15-20% Pb 2 O 5 , 4-8% TiO 2 4-10% B 2 O 3 and 15-28% TeO 3, that is, in terms of mass percentage, the glass powder is composed of 15-25% Bi 2 O 3 , 4-8% Al 2 O 3 , 6~12% SiO 2 , 10-29% ZnO, 15-20% Pb 2 O 5 , 4-8% TiO 2 4-10% B 2 O 3 and 15-28% TeO 3 The glass powder is obtained by sintering and pulverizing, and the D50 of the glass powder is 1.8-2.2 μm, and the glass activity is moderate. Optionally, the D50 of the glass powder is 1.9-2.1 μm.
[0061] Among them, Bi 2 O 3 As the main network structure; Al 2 O 3 Can adjust glass stability and increase viscosity; SiO 2 As a glass network former, it promotes glass stability and lowers the glass melting point; ZnO can break the network structure and promote glass crystallization; Pb 2 O 5 Reacts with silicon nitride to generate lead, nitrogen and silicon dioxide; TiO 2 For local crystallization; B 2 O 3 Used to provide trace amounts of boron; TeO 3 Used for local microcrystals to lower the melting point.
[0062] The embodiment of the present invention also provides a method for preparing silver-aluminum paste for N-type IBC battery, wherein: Figure 1 As shown, it includes steps 101 to 102:
[0063] Step 101: Mix boron powder, gallium powder and an organic binder to obtain a first mixture;
[0064] Step 101, adding silver powder, aluminum powder and glass powder to the first mixture, mixing well, to obtain a second mixture;
[0065] Step 102: Grind the second mixture, add an organic additive, and obtain silver-aluminum paste for N-type IBC batteries.
[0066] In the above step 101, 0.1-0.3% of boron powder, 0.1-0.2% of gallium powder, and 15.5-30.2% of organic binder accounting for the total mass of the raw materials are weighed, mixed, and dispersed using a disperser to obtain the above first mixture.
[0067] In the above step 102, 65-75% of silver powder, 2-5% of aluminum powder, and 1.8-2.5% of glass powder accounting for the total mass of the raw materials are weighed and mixed, and dispersed by a disperser to obtain the above second mixture.
[0068] In the above step 102, the above second mixture is ground and then an organic additive accounting for 0.8 to 1.5% of the total mass of the raw materials is added. After high-speed dispersion, a positive electrode grid line that contacts the P+ area on the back of the N-type IBC battery is obtained without the need for laser grooving, thereby avoiding damage to the passivation layer caused by laser grooving.
[0069] In the embodiment of the present invention, silver powder, boron powder and gallium powder are added to the positive electrode grid line slurry; wherein, the boron element in the boron powder can increase the doping of the P+ region; gallium and aluminum are both third main group elements, have similar chemical properties to aluminum, and can replace part of the aluminum powder; and the silver powder has an etching effect, after forming a passivation layer on the back of the battery silicon wafer, it is directly printed on the passivation layer area above the p+ doped area, and then subjected to high-temperature sintering, it can contact with the p+ doped area and form a positive electrode grid line, eliminating the step of secondary laser grooving, avoiding the damage of the passivation layer caused by the secondary laser grooving, and can improve the battery open circuit voltage; at the same time, the specific gravity of gallium is relatively large, in During the sintering process, aluminum quickly descends to the silicon surface, which increases the probability of Ga-Si contact, reduces aluminum as a recombination center, reduces the contact resistance between the slurry and the battery, and can maintain a relatively high open circuit voltage. In addition, gallium is used to replace part of the aluminum powder to reduce the aluminum content, which is beneficial to reduce the side effects of Al, weakening the Al-Si reaction, forming shallower silver-aluminum corrosion pits and reducing recombination, thereby improving the open circuit voltage and efficiency of the battery. This solves the problem that the existing N-type IBC battery aluminum paste needs to be laser grooved in the P+ area before printing the positive grid line, and is prone to form metal recombination centers, resulting in a decrease in the open circuit voltage of the battery cell.
[0070] Optionally, in the preparation method provided in the embodiment of the present invention, the boron powder is micron-sized boron aluminum alloy and / or micron-sized elemental boron. Micron-sized boron aluminum alloy and micron-sized elemental boron have the characteristics of high tap density, low oxygen content and high activity. By adding the micron-sized boron aluminum alloy powder and / or micron-sized elemental boron, the aluminum paste can quickly form a good alloy with silicon under low sintering temperature conditions, thereby reducing the contact resistivity between the front aluminum fine grid and the battery.
[0071] Optionally, in the preparation method provided in an embodiment of the present invention, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.
[0072] Optionally, in the preparation method provided in the embodiment of the present invention, the silver powder includes micron-spherical silver powder and nano-spherical silver powder;
[0073] And / or the aluminum powder includes micron-sized spherical aluminum powder with a mass fraction of 82-92% and a D50 of 5-6 μm, and micron-sized spherical aluminum powder with a mass fraction of 8-18% and a D50 of 9-10 μm.
[0074] Optionally, in a specific embodiment, the silver powder includes 82-92% by mass of micron-sized spherical silver powder and 8-18% by mass of nano-sized spherical silver powder.
[0075] Optionally, in the preparation method provided in the embodiment of the present invention, the glass powder is composed of 15-25% Bi 2 O 3 , 4-8% Al 2 O 3 , 6~12% SiO 2 , 10-29% ZnO, 15-20% Pb 2 O 5 , 4-8% TiO 2 4-10% B 2 O 3 and 15-28% TeO 3 Obtained by sintering and crushing.
[0076] Optionally, in the preparation method provided in the embodiment of the present invention, the gallium powder is micron-sized single-element gallium or gallium-aluminum alloy.
[0077] Optionally, in the preparation method provided in an embodiment of the present invention, the organic auxiliary agent includes one or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.
[0078] Optionally, in the preparation method provided in the embodiment of the present invention, the organic binder comprises a high molecular polymer resin and an organic solvent;
[0079] The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%;
[0080] The mass fraction of the organic solvent in the organic binder is 88-92%.
[0081] Optionally, in the preparation method provided in the embodiment of the present invention, the high molecular polymer is resin-50;
[0082] The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0083] The present invention also provides a method for preparing an N-type IBC battery, wherein: Figure 2 As shown, it includes steps 201 to 203:
[0084] Step 201, after forming interdigitated n+ doped regions and p+ doped regions on the back side of an N-type silicon wafer, a passivation layer is formed on the surfaces of the n+ doped regions and the p+ doped regions;
[0085] Step 202, printing silver-aluminum paste on a first region of the passivation layer, and printing silver paste on a second region of the passivation layer; the projection of the first region is within the range of the p+ doped region, and the projection of the second region is within the range of the n+ doped region; wherein the components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder;
[0086] Step 203 , high-temperature sintering is performed on the N-type silicon wafer with silver-aluminum paste printed on the first region and silver paste printed on the second region to obtain an IBC battery.
[0087] In the above step 201, the silicon wafer is firstly subjected to alkali texturing, and then an n+ doped region and a p+ doped region arranged in a finger-like manner are formed on the back of the silicon wafer, and then a silicon oxide layer or a silicon nitride layer is deposited to cover the entire back of the silicon wafer as the above passivation layer.
[0088] Among them, the P+ doping area is formed by boron diffusion and laser SE process on N-type silicon wafer to further reduce metal recombination and increase the opening voltage.
[0089] In the above step 202, the silicon wafer after the passivation layer is formed is screen-printed to prepare the electrode grid lines. Specifically, the silver-aluminum paste is printed on the first area of the passivation layer on the back of the silicon wafer, and the projection of the first area is within the p+ doped area to form a positive grid line that is conductive with the p+ doped area; at the same time, the silver paste needs to be printed on the second area of the back passivation layer, and the projection of the second area is within the n+ doped area to form a negative grid line spaced from the positive grid line, wherein the silver paste can be a traditional silver paste.
[0090] In the above step 203, because silver powder and gallium powder are added to the silver-aluminum paste, gallium and aluminum are both third main group elements, have similar chemical properties to aluminum, and can replace part of the aluminum powder; and the silver powder has a burn-through effect. After forming a passivation layer on the back of the battery silicon wafer, it is directly printed on the passivation layer area above the p+ doped area, and then sintered at high temperature, it can contact with the p+ doped area and form a positive grid line, eliminating the step of secondary laser grooving, avoiding the damage of the passivation layer caused by the secondary laser grooving, and can improve the battery open circuit voltage; at the same time, gallium has a larger specific gravity and drops to the silicon surface faster than aluminum during the sintering process, so that the Ga-Si contact probability is increased, reducing aluminum as a recombination center, reducing the contact resistance between the slurry and the battery, and maintaining a higher open circuit voltage; in addition, using gallium to replace part of the aluminum powder reduces the aluminum content, which is beneficial to reducing the side effects of Al, weakening the Al-Si reaction, and forming a shallow silver-aluminum corrosion pit and reducing recombination, thereby improving the battery open circuit voltage and efficiency.
[0091] The present invention is described in detail below by way of examples.
[0092] Example 1
[0093] (1) providing a silver-aluminum paste: the silver-aluminum paste is composed of 1.2 parts of an organic additive, 70 parts of silver powder, 3 parts of aluminum powder, 0.1 parts of boron powder, 0.1 parts of gallium powder, 23.6 parts of an organic binder and 2 parts of glass powder, by weight;
[0094] The organic additives include three of silane coupling agents, silicone oil, and a mixture of lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 nines and a mass fraction of 90%, and nano-spherical silver powder with a purity of 3 nines and a mass fraction of 10%; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 85% and a D50 of 5 to 6 μm, and micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 15% and a D50 of 9 to 10 μm; the organic binder includes resin-50 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent includes benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, and tributyl citrate;
[0095] The glass powder is composed of 20% by mass of Bi 2 O 3 , 7% Al 2 O 3 , 10% SiO 2 , 10% ZnO, 20% Sb 2 O 5 , 8% TiO 2 6% B 2 O 3 , 19%TeO 3Obtained by sintering and crushing.
[0096] (2) After forming a silicon oxide layer and a polysilicon layer on the back side of an N-type silicon wafer with a size of 182 mm × 182 mm, the back polysilicon layer is subjected to boron diffusion and laser SE treatment;
[0097] (3) laser grooving the back side of the phosphorus-doped N-type silicon wafer to form interdigitated n+ doped regions and p+ doped regions, and removing the front polysilicon layer;
[0098] (4) after removing the front polysilicon layer and sequentially forming a double-sided aluminum oxide layer, a front silicon nitride layer, and a back silicon nitride layer, the silver-aluminum paste is printed on the back silicon nitride layer opposite to the p+ doped region by a 480-mesh screen, and the silver paste is printed on the back silicon nitride layer opposite to the n+ doped region;
[0099] (5) The silicon wafer is sintered at a high temperature in a sintering furnace, with a peak sintering temperature of 778° C., to produce an N-type IBC battery.
[0100] Example 2
[0101] The difference between Example 2 and Example 1 is that in step (1), the silver-aluminum paste consists of 0.8 parts of organic additives, 75 parts of silver powder, 2 parts of aluminum powder, 0.3 parts of boron powder, 0.1 parts of gallium powder, 20 parts of organic binder and 1.8 parts of glass powder, by mass.
[0102] Example 3
[0103] The difference between Example 3 and Example 1 is that in step (1), the silver-aluminum paste consists of 1.5 parts of organic additives, 65 parts of silver powder, 5 parts of aluminum powder, 0.1 parts of boron powder, 0.2 parts of gallium powder, 25.7 parts of organic binder and 2.5 parts of glass powder, by mass.
[0104] Example 4
[0105] The difference between Example 4 and Example 1 is that in step (1), the silver-aluminum paste consists of 1.5 parts of organic additives, 75 parts of silver powder, 5 parts of aluminum powder, 0.3 parts of boron powder, 0.2 parts of gallium powder, 15.5 parts of organic binder and 2.5 parts of glass powder, by mass.
[0106] Example 5
[0107] The difference between Example 3 and Example 1 is that in step (1), the silver-aluminum paste consists of 0.8 parts of organic additives, 65 parts of silver powder, 2 parts of aluminum powder, 0.1 parts of boron powder, 0.1 parts of gallium powder, 30.2 parts of organic binder and 1.8 parts of glass powder, by mass.
[0108] Example 6
[0109] The difference between Example 6 and Example 1 is that in step (1), the silver-aluminum paste is composed of 1.1 parts of organic additives, 70 parts of silver powder, 3 parts of aluminum powder, 0.2 parts of boron powder, 0.15 parts of gallium powder, 23.45 parts of organic binder and 2.1 parts of glass powder, by mass.
[0110] Comparative Example 1
[0111] The difference between Comparative Example 1 and Example 1 is that in step (1), the silver-aluminum paste consists of 1.1 parts of organic additives, 70 parts of silver powder, 3.35 parts of aluminum powder, 23.45 parts of organic binder and 2.1 parts of glass powder, by mass.
[0112] Comparative Example 2
[0113] (1) providing a silver-aluminum paste: the silver-aluminum paste is composed of 1.2 parts of an organic additive, 73.35 parts of aluminum powder, 23.6 parts of an organic binder, and 2 parts of glass powder, by weight;
[0114] The organic additives include three of silane coupling agents, silicone oil, and a mixture of lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 nines and a mass fraction of 90%, and nano-spherical silver powder with a purity of 3 nines and a mass fraction of 10%; the aluminum powder includes micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 85% and a D50 of 5 to 6 μm, and micron-grade spherical aluminum powder with a purity of 3 nines and a mass fraction of 15% and a D50 of 9 to 10 μm; the organic binder includes resin-50 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent includes benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, and tributyl citrate;
[0115] The glass powder is composed of 20% by mass of Bi 2 O 3 , 7% AL 2 O 3 , 10% SiO 2 , 10% ZnO, 20% Sb 2 O 5 , 8% TiO, 6% B 2 O 3 , 19%TeO 3 Obtained by sintering and crushing.
[0116] (2) After forming a silicon oxide layer and a polysilicon layer on the back side of an N-type silicon wafer with a size of 182 mm × 182 mm, the back polysilicon layer is subjected to boron diffusion and laser SE treatment;
[0117] (3) laser grooving the back side of the phosphorus-doped N-type silicon wafer to form interdigitated n+ doped regions and p+ doped regions, and removing the front polysilicon layer;
[0118] (4) after removing the front polysilicon layer and sequentially forming a double-sided aluminum oxide layer, a front silicon nitride layer, and a back silicon nitride layer, laser grooving is performed on the back region directly opposite to the p+ doped region to form a first opening that is conductive to the p+ doped region, and the above-mentioned silver aluminum paste is printed at the first opening by 480 mesh screen printing, and silver paste is printed on the back silicon nitride directly opposite to the n+ doped region;
[0119] (5) The silicon wafer is sintered at a high temperature in a sintering furnace, with a peak sintering temperature of 778° C., to produce an N-type IBC battery.
[0120] The electrical performance of the N-type IBC batteries prepared in the above embodiments and comparative examples was tested, and the results are shown in Table 1 below:
[0121] Table 1
[0122]
[0123] By comparing Examples 1 to 6 with Comparative Examples 1 and 2, it can be seen that by forming the P+ emitter using silver-aluminum paste doped with indium and boron, not only can the back pole grid line be formed without laser grooving, but the recombination rate and degree of the battery will also be greatly improved, the efficiency of the battery is increased by 0.35%, and the start-up voltage is increased by 8mv.
[0124] In summary, in this embodiment, silver powder, boron powder and gallium powder are added to the positive electrode grid line paste; wherein, the boron element in the boron powder can increase the doping of the P+ region; gallium and aluminum are both third main group elements, and have similar chemical properties to aluminum, and can replace part of the aluminum powder; and the silver powder has an etching effect. After the passivation layer is formed on the back of the battery silicon wafer, it is directly printed on the passivation layer area above the p+ doped area, and then sintered at a high temperature, it can contact with the p+ doped area and form the positive electrode grid line, eliminating the step of secondary laser grooving, avoiding the damage of the passivation layer caused by the secondary laser grooving, and can improve the battery open circuit voltage; at the same time, the specific gravity of gallium is relatively high. During the sintering process, the silver-aluminum alloy is larger and falls to the silicon surface faster than aluminum, which increases the probability of Ga-Si contact, reduces aluminum as a recombination center, reduces the contact resistance between the slurry and the battery, and can maintain a relatively high open circuit voltage. In addition, gallium is used to replace part of the aluminum powder to reduce the aluminum content, which is beneficial to reduce the side effects of Al, weaken the Al-Si reaction, and form shallow silver-aluminum corrosion pits and reduce recombination, thereby improving the open circuit voltage and efficiency of the battery. This solves the problem that the existing N-type IBC battery aluminum paste needs to be laser grooved in the P+ area before printing the positive grid line, and is prone to form a metal recombination center, resulting in a decrease in the open circuit voltage value of the battery cell.
[0125] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0126] The above is a detailed introduction to the silver-aluminum paste for the positive grid line of an N-type IBC battery, an N-type IBC battery and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A silver-aluminum paste for positive grid lines of N-type IBC batteries, characterized in that: The components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder.
2. The silver-aluminum paste for N-type IBC battery according to claim 1, characterized in that: The mass fractions of the organic additive, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder are 0.8-1.5%, 65-75%, 2-5%, 0.1-0.3%, 0.1-0.2%, 15.5-30.2% and 1.8-2.5% respectively.
3. The silver-aluminum paste according to claim 1, characterized in that: The glass powder comprises 15-25% by mass of Bi2O3, 4-8% by mass of Al2O3, 6-12% by mass of SiO2, 10-29% by mass of ZnO, 15-20% by mass of Pb2O5, 4-8% by mass of TiO2, 4-10% by mass of B2O3 and 15-28% by mass of TeO3.
4. The silver-aluminum paste according to claim 1, characterized in that: The gallium powder is single-element gallium.
5. The silver-aluminum paste according to claim 1, characterized in that: The organic auxiliary agent includes one or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate mixture.
6. The silver-aluminum paste according to claim 5, characterized in that: The organic binder includes a high molecular polymer resin and an organic solvent; The mass fraction of the high molecular weight polymer in the organic binder is 8 to 12%; The mass fraction of the organic solvent in the organic binder is 88-92%.
7. The silver-aluminum paste according to claim 6, characterized in that: The high molecular polymer is resin-50; The organic solvent includes at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
8. The silver-aluminum paste according to claim 1, characterized in that: The silver powder includes micron-spherical silver powder and nano-spherical silver powder; And / or the aluminum powder includes micron-sized spherical aluminum powder with a mass fraction of 82-92% and a D50 of 5-6 μm, and micron-sized spherical aluminum powder with a mass fraction of 8-18% and a D50 of 9-10 μm.
9. A method for preparing an N-type IBC battery, characterized in that: include: After forming an n+ doped region and a p+ doped region arranged in an interdigitated manner on the back of an N-type silicon wafer, a passivation layer is formed on the surface of the n+ doped region and the p+ doped region; Printing silver-aluminum paste on a first region of the passivation layer, and printing silver paste on a second region of the passivation layer; The projection of the first region is within the range of the p+ doped region, and the projection of the second region is within the range of the n+ doped region; wherein the components constituting the silver-aluminum paste include organic additives, silver powder, aluminum powder, boron powder, gallium powder, organic adhesive and glass powder; The N-type silicon wafer with silver-aluminum paste printed on the first area and silver paste printed on the second area is sintered at high temperature to produce an IBC battery.
10. An N-type IBC battery, characterized in that: The method according to claim 9 is used to prepare the product.
Citation Information
Patent Citations
Electric conduction slurry and application of electric conduction slurry in N type silicon wafer solar cells
CN104795127A
Positive silver paste suitable for positive aluminum oxide-silicon nitride laminated passivation crystalline silicon solar cell and preparation method of positive silver paste
CN111128436A
Preparation method of aluminum paste for improving efficiency of double-sided PERC battery
CN111403076A
Front aluminum paste suitable for N-type TOPCon battery and preparation method of front aluminum paste
CN114203335A
Low-temperature sintered silver-aluminum paste for N-TOPCon solar cell and preparation method and application of low-temperature sintered silver-aluminum paste
CN115732118A
